“Estudio tecnológico para la obtención de harina a partir de cormo de jergón sacha ( dracontium sp.) para consumo humano” - Bernales García, Robert Cristian (2002)
The present study, was carried out in the laboratories of Analysis and Composition of Agroindustrial Products (ANACOMPA), Agroindustrial Products Technology of non Food (TEPANAL), Laboratory of Engineering and Design of the faculty of Agroindustrial Engineering of the San Martín National University. The research found for to even incentivate the use of the no exploted wild cultivations, like it is the case of the Jergón Sacha's (Dracontium sp.), which are distributed in the whole Amazonía, in cultivated or wild form, being used totally for the cure of diverse illnesses. The study understand diversa analysis, so much of the matter prevails as of the finished product, as well as the necessary chemical and sensorial analyses. The samples of Jergón Sacha's cormo ( Dracontiun sp.), were collected in the town of Pamashto, located to 1 O Km of province of lamas zone, with minimum temperature of 17 ºC and maximum of 20ºC, located to a height of 800 m.s.n.m. the cormos was harvested talking of account of size that were approximately from 15 to 20 cm and 6 months of period. The cormos presentad a pale yellow - orange color, according to the table of standar color by Ridguay (1912), circulate flat shape, with diameter average of 17.1 cm and thickness average of 7.45 cm, the density average were 1.066 gr /cm3, the chemical determination gave, proximal composition with humidity 71. 72%, protein 1.97%, carbohydrates 25.2%, fat 0.11 %, fiber 0.16% and ashy 0.83%. The pH was 6.68 and the acidity gave 0.048%. The raw material was receptiomed in the laboratories of the faculty of agroindustrial engineering after proceeded to sample's laundry for elimination of impurities, them it peeled with help of a knife of stainless steel, after it was cut or laminate with help of a handy cutter that has an approximate thickness , to 2 mm, at once it was washed of flakes with water at atmosphere temperature using a totally randomized design with factorial arrangement 3x3 to eliminate of pungent and astringent substances of spice, after evaluated with a sensorial panel to hedonic scale with 5 points, that was evaluated the attribute flavor, giving as a result; that major part of these substances eliminate with a washed of 1 O hours and a relation water I matter of 9/1, with changa of water each half - hour, immediately was proceeded to the dried, using totally randomized design with factorial arrangement too for determining the better conditions of dried for the final product. lt was carried out a sensorial evaluation with hedonic scale of 5 points, through which were evaluated characteristics of color, odor and general appearance. The results indicated that best treatment was 50°C, air velocity 1.1 mis. The values of diffusivity increased 3.44 x 1010 m2/s, with conditions of 40°C and 0.5 m/s of dried air velocity, to 9.52 x 1010 m2/s, with conditions of SOºC and 1.1 mis of dried air velocity. Then was proceeded to the milling of dried flakes inside of a mili trademark. Crolum, immediately proceeded to sift them to uniformize the particles obtained and were packed in high density polyetileme bags to avoid possible deterioration of product. The process flux for the obtaining of flour of Jergón Sacha's cormo flour (Dracontium sp.) is the following: Raw Material ----- Sample's Laundry Peeled Weighed Cut Washed of Flakes Dried Milling -----Sifted----- Packed. After on the proximal composition of the finished product was determinad giving as a result, humidity 10%, protein 3.47%, fiber 2.03%, ash 1.44%, fat 0.94%, carbohydrates 81.36%. The pH was 6.38 and the acidity gave 0.095% named as sulfuric acid. The microbiológical analysis gave values into the range recommended by DIGESA with that has been demonstrated the quality and asepticism of the process, and its yield was 24%. The flours presentad a Light Buff color, according to the table of standar color by Ridguay (1912).